The Power of Geography : Ten Maps That Reveal The Future of Our World - Marshall, Tim (New York : Elliott & Thompson, 2021)
"Tim Marshall's global bestseller Prisoners of Geography offered us a "fresh way of looking at maps" (The New York Times Book Review), showing how every nation's choices are limited by mountains, rivers, seas and concrete. Since then, the geography hasn't changed, but the world has. Now, in this revelatory new book, Marshall takes us into ten regions that are set to shape global politics and power. Find out why the Earth's atmosphere is the world's next battleground; why the fight for the Pacific is just beginning; and why Europe's next refugee crisis is closer than we think. In ten chapters covering Australia, The Sahel, Greece, Turkey, the UK, Iran, Ethiopia, Saudi Arabia, Spain and Space, Marshall explains how a region's geography and physical characteristics affect the decisions made by its leaders. Innovative, compelling, and delivered with Marshall's trademark wit and insight, this is a gripping and enlightening exploration of the power of geography to shape humanity's past, present, and-most importantly-our future"--
1. Australia 2. Iran 3. Saudi Arabia 4. The United Kingdom 5. Greece 6. Turkey 7. The Sahel 8. Ethiopia 9. Spain 10. Space
Keywords: Geopolitics, World politics